2016
DOI: 10.1080/13548506.2016.1163399
|View full text |Cite
|
Sign up to set email alerts
|

Implicit attitudes towards people with visible difference: findings from an Implicit Association Test

Abstract: Research on implicit and explicit attitudes towards those with a visible difference has provided contradictory findings. While studies suggest explicit attitudes towards those with a visible difference are positive, implicit attitudes are likely to be negative. An Implicit Association Test measured attitudes towards visible differences in 129 adults finding no evidence of negative implicit attitudes. This contrasts with previous findings and accounts of those with a visible difference who report perceiving neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Additionally, social desirability bias could have influenced the results, as pointed out in previous studies [26,[51][52][53]. Future studies may consider to use less biased measurement methods, such as the implicit association test for measuring stigma [51,[54][55][56].…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, social desirability bias could have influenced the results, as pointed out in previous studies [26,[51][52][53]. Future studies may consider to use less biased measurement methods, such as the implicit association test for measuring stigma [51,[54][55][56].…”
Section: Discussionmentioning
confidence: 89%
“…Turning to people with disabilities, Leslie perceived the roots of prejudicial attitudes as belonging to the following categories: 1) social customs and norms; 2) child-rearing practices; 3) recurrence of childhood fears in frustrating/anxiety-provoking situations; and (4) discrimination-provoking behavior by persons with disabilities [14]. Finally, sources of negative attitudes toward persons with disabilities occur along six dimensions that include sociocultural, psychological, affective-cognitive, conscious-unconscious, past experience-present situation, internally originated-externally originated, and theoretical-empirical [15][16][17][18].…”
Section: Attitude Formationmentioning
confidence: 99%
“…Perhaps as a result of this complexity, there is no current consensus on how to measure or address the psychological impact of visible difference on individuals, 4 and specialist provision of psychological support varies even within Europe 5 . Importantly, however, it has recently been shown that implicit attitudes towards those with visible difference may not be negative, and resultant behaviors from the public may result from uncertainty regarding how to behave, rather than negative perceptions 6 . Public education is therefore likely to be as relevant as psychological support of the individual.…”
Section: Introductionmentioning
confidence: 99%
“…5 Importantly, however, it has recently been shown that implicit attitudes towards those with visible difference may not be negative, and resultant behaviors from the public may result from uncertainty regarding how to behave, rather than negative perceptions. 6 Public education is therefore likely to be as relevant as psychological support of the individual.…”
mentioning
confidence: 99%